Manejo de existencia e inventario en el área de bodega de la Ferretería Hermanos Chimbo del cantón Pueblo Viejo - Salmon Barzola, Gustavo Adrián (2020)
The “Hermanos Chimbo” hardware store in the Puebloviejo canton is a company dedicated to the sale of hardware materials to the inhabitants of the town and neighboring sectors; The problem presented by the organization lies in the empirical administration, because they do not have a human talent trained in the development of administrative and accounting activities, the main cause of which is that there are weaknesses in inventory and existence management. The control of material assets of the organization is carried out manually, without establishing the necessary tools for the proper registration of the entry and exit of assets, a situation that has caused the decision-making process to be inadequate, due to that ineffective inventory control affects the financial management of the institution. The case study is structured by means of descriptive and documentary research, inductive method, survey, direct observation and as research instruments the questionnaire and registration form, where the results are that the organization does not use the use of a Weighted average method for inventory control, where inadequate inventory management responds to the organization's human talent job profile.